Witness intimidation in the industrial court - Boxall, T J (Centre for Law and Society, 2023)
It is in the nature of adversarial proceedings that parties are set against each other, challenging versions of fact and arguing points of law in competition with each other. They do so before a person or persons appointed to listen, to weigh and to decide which versions and arguments should prevail. Witnesses called to give evidence by one or other party are inevitably involved in the muscular give and take of the competition. The process is a robust one and its value to a measure depends on the commitment of the various parties to their positions and their willingness to express these freely and without compromise in the presence of those who challenge them. It requires courage. For many people the experience of giving evidence in court comes as an unpleasant shock, meeting, as they do, not the accommodation and trust that they are used to in their daily dealings but doubt, mistrust and opposition. Insofar as their evidence is to the detriment of another, they speak in the knowledge of cultivating enmity and possibly of inviting reprisal. It says a great deal for the respect accorded to the law and its processes and for people's desire for justice that adversarial proceedings do not generally find that courage lacking.